EVALUATION OF RISKS RELATED TO RUSSIAN POWER GRID COMPANIES BY FOREIGN INVESTORS - D. L. Valkova (Vestnik MGIMO-Universiteta)
The article focuses on the impact of the current crisis on evaluation of risks related to Russian power grid companies by foreign investors as well as on prospects of raising foreign capital. The current situation resulted in a considerable deterioration of investment climate in Russia as well as in aggravation of industry-specific problems. Inflation growth, devaluation of the national currency, GDP decrease, drop in electricity consumption and the crisis in the banking sector negatively impact the investment profile of the country. This leads to increased risk premium for foreign capital investments in any type of Russian assets. At the same time industry-specific problems augmented as well. Those are primarily lack of transparency in regulation, which is subject to constant changes, growth in overdue receivables, limited access to modern technologies. All of the above had a considerable impact on the perception of Russian risks by international investors. A comprehensive approach is needed to improve the investment climate in the country and this would be largely defined by the general macroeconomic development of the Russian Federation and relations with other states. Consistent strategy and integrated actions of the Government and respective Ministries are of particular importance. As for the industry-specific factors, transparent and well-balanced long-term tariff system is the key condition for sustainable improvement of the situation in the sector, according to the major industry participants and leading experts. Thus, the article highlights changes in investor perception of the Russian power grid sector as well as relative impact on the industry development prospects. This analysis is the basis for further elaboration of recommendations regarding easing off of the crisis impact on the power grid companies as well as for assessment of prospects of meeting strategic industry development objectives.